Karakteristik gejala Computer Vision Syndrom (CVS) pada pekerja bidang pendidikan - Prasetyaningsih, Noviani; Hartanti, Monica Dwi; Adiwardhani, Anggraeni; Samira, Jihan (Fakultas Kedokteran Universitas Trisakti, 2022)
BACKGROUNDThe frequency and duration of using electronic devices have increased rapidly due to working from home during the Covid19 pandemic. This causes many complaints of vision such as tired eyes, heat, blur, foreign body sensation in the eyes and various other symptoms. All of these are known as Computer Vision Syndrome (CVS) symptoms, which could happen in and/or outside the eye. This study aims to analyze the relationship between the use of electronic devices with CVS symptoms felt by employees of the Faculty of Medicine, Universitas Trisakti, Jakarta. METHODSFifty-three employees aged 25-60; were recruited for this cross-sectional study. A complete questionnaire consisting of several questions, including the type and number of electronic devices used, how many hours of use in a day, and complaints felt when using electronic devices, was applied to determine the CVS symptoms. In addition, a visual inspection was conducted to determine the visual acuity. Fisher's exact test was used for analyzing the statistics. RESULTSMore than half of the subjects (52.8%) used 3-4 electronic devices for more than 6 hours daily (56.6%). Multiple CVS symptoms were complaint by 52.83% of subjects, such as tired eyes, blurred vision, and dry eyes observed in 71.7%, 45.3%, and 33.9% of subjects, respectively. Bivariate analysis using Fisher's exact test assessed the relationship between risk factors, such as the use of electronic devices, gender, age, number of electronic devices used, duration of usage in a day, visual acuity, and the incidence of CVS complaints. There was no significant relationship between the various risk factors with CVS complaints, indicated by p>0.05 in all variables. CONCLUSIONUsers of electronic devices often feel various complaints in their eyes when using these devices. Although there was no association between the risk factors studied and complaints of CVS, it is still critical to investigate other factors that may be associated with the incidence of CVS due to its multifactorial pathogenesis. KEYWORDS: Computer Vision Syndrom, CVS, Electronic Devices, Vision